PERBANDINGAN ANTARA TREN PERPUSTAKAAN, LITERASI, DAN REVOLUSI INDUSTRI 4.0 PADA MESIN PENCARI GOOGLE - Prasetyo Adi (Perpustakaan Nasional RI, 2020)
Introduction. Literacy level has an impact on economic development of a country. The lack of literacy is a barrier to one’s development in their life stages. Library then helps people to improve their literacy. Digital industry has changed the library’s services and collections. Tujuan. The study aims to observe the comparison of library searching trend, literacy and Google on industrial revolution 4.0. Metode. This is a qualitative study with survey from Google trends as its based approach. The samples were data of the trend number about “library”, “literacy” and “industrial revolution 4.0”. Results. The results of the study showed that the trend value of information searching about “library” is not always in line with the trend “literacy”. Moreover, both trends have no impact on information searching trend about “industrial revolution 4.0”.